USING WRITE-AROUND STRATEGY TO IMPROVE THE RECOUNT TEXT WRITING SKILL OF THE TENTH GRADERS OF SMA EL-SHADAI MAGELANG IN THE SCHOOL YEAR 2017/2018 - Ilham Satrio Anggoro (Faculty of Education and Teachers Training, 2020)
Writing is one of the skill which is very important to be learnt because it is a process of expressing idea, opinion, information in written language. Based on writer observation on the tenth graders of SMA El Shadai Magelang, the students writing skills of recount text is not satisfactory yet. The average score of recount writing test is 63.53 less than standart minimum score which is 75.This research is a Classroom Action Research. It devided into three steps, there are Pre cycle, cycle I, and cycle II. The Writer takes the X MIA of SMA El Shadai Magelang in school year 2017/2018 as the subject of the research. There are consist of 15 students. 7 male and 8 female. The technique of collecting data is using test and non test data.As the result, the writer found that using Write Around Strategy in teaching recount text writing skill of the tenth graders of SMA El Shadai Magelang have made improvement in their learning motivation.The result of the observation, the writer found that the students are passive and do not anthusiastically during teaching learning process. After they taught by using this strategy, it allows students behavior to be positive behaviour. They were more interested in writing recount text and more enthusiasm in teching learning process.Then the result of the test, the students average score of all cycle; Pre Cylce (63.53), Cycle I (70.73), Cycle II (81).